(untitled) (Indian Journal of Arid Horticulture, 2017)
An experiment was conducted to study the influence of different media and growth regulators on the rooting and sprouting of hardwood cuttings of pomegranate cv. Bhagwa. Hardwood cuttings of diameter 0.8-1.0 cm having length 20-25 cm were taken and subjected to following treatments, viz., NAA-2500 ppm (T1), NAA-5000 ppm (T2), distilled water without growth regulator as control (T3), Seradex rooting powder (T4), IBA-2500 ppm (Ts) and IBA-5000 ppm (T6) and then planted in vermiculite (M1), cocopeat (M2), sand (M3) and soil (M4) as rooting media. The results clearly demonstrate that cocopeat showed significantly higher bud sprout (5.54), shoot length (21.35 cm), root length (17.48 cm) and survival per cent (74.17) of hardwood cuttings. Among the different growth regulator maximum number of sprouts (4.88), shoot length (22.93 cm), root length (19.54 cm) and per cent survivability (73.0%) were registered with IBA 5000 ppm treatment. The interaction of cocopeat + IBA 5000 ppm was found to be most effective for encouraging the number of shoots (7.60), shoot length (26.70 cm), root length (25.60 cm), survivability of cuttings (85%) and root density.